2020
DOI: 10.1089/tmj.2019.0237
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Patient Portal Use on Duplicate Laboratory Tests in Diabetes Management

Abstract: Background: Patients seek care across multiple health care settings. One coordination issue is the unnecessary duplication of laboratory across different health care settings. This analysis examined the association between patient portal use and duplication of laboratory testing among Veterans who are dual users of Veterans Affairs (VA) and non-VA providers. Materials and Methods: A national sample of Veterans who were newly authenticated users of the portal during fiscal year (FY) 2013 who used Blue Button at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…In the updated search in August 2023, OP and WG independently screened titles and abstracts, followed by an independent review of the selected full texts, and disagreements were resolved by consensus. During this stage, 7 articles met the inclusion criteria [19,[44][45][46][47][48][49]. A list of articles compiled by OP during the ongoing monitoring of new publications from September 2020 to August 2023 was compared with the results of the updated search, and 2 new articles [50,51] meeting the inclusion criteria were added.…”
Section: Study Selectionmentioning
confidence: 99%
“…In the updated search in August 2023, OP and WG independently screened titles and abstracts, followed by an independent review of the selected full texts, and disagreements were resolved by consensus. During this stage, 7 articles met the inclusion criteria [19,[44][45][46][47][48][49]. A list of articles compiled by OP during the ongoing monitoring of new publications from September 2020 to August 2023 was compared with the results of the updated search, and 2 new articles [50,51] meeting the inclusion criteria were added.…”
Section: Study Selectionmentioning
confidence: 99%
“…26 Last, a study of the Blue Button feature (n ¼ 3762 users, 26 424 nonusers) found that Blue Button users had lower odds of duplicate HbA1c testing compared with nonusers. 27 Studies outside the VHA have also found a relationship between portal use and positive health outcomes among patients with diabetes. Secure message intensity has been associated with better glycemic control and increased outpatient utilization.…”
Section: Introductionmentioning
confidence: 99%
“…Comprehensive patient portals that enable access to data from multiple health services (ie, internal and external laboratories, diagnostic images, and discharge reports) have been shown to reduce duplicate testing [ 11 ] and enhance communication [ 12 , 13 ]. The primary argument for patient portals is not that they intend to create value for money; rather, they foster patient empowerment and self-management and improve patients’ engagement in their care [ 14 ].…”
Section: Introductionmentioning
confidence: 99%